Il Cammin di Nostra Lingua: Ruggero Bonghi and the questione della lingua - Campanelli, L (2020)
In Italian history, the Risorgimento represents not only the push for political unification but a process of social change that manifested itself in the efforts to establish a national identity, develop a centralized system of government, and implement a comprehensive system of education. With the promulgation of a standardized language as the most fundamental component of achieving any degree of political, social, or educational cohesion, the nineteenth-century questione della lingua demonstrates – more than in any other period in Italian history – the interconnected nature of linguistic, literary, social, political, and economic cultures. It is precisely in this capacity that an analysis of a historical figure such as Ruggero Bonghi – who operated as a journalist, academic, and politician in equal capacities – provides incomparable insight into the extent to which the questione della lingua shaped every facet of Italian society. As someone who began engaging with the issue from the early 1850s – prior to Italy’s political unification – and continued working on initiatives pertaining to education until the 1890s – over three decades following the nation’s first piece of national educational legislation – Bonghi’s ideas and methods of addressing Italy’s linguistic, literary, and socio-political formation developed alongside the evolution of the language debate itself. This comprehensive study on Ruggero Bonghi and his involvement with the questione della lingua serves to not only elucidate the historical significance of a figure who has been largely overlooked in contemporary scholarship but also demonstrate – through the life and career of one particular individual who operated in both a literary and political perspective – the extent to which the language debate in Italy shaped more than simply the nation’s means of linguistic or artistic expression.